ヒガシ オングルトウ ノ ドジョウ カンキョウ - 唐沢, 栄; カラサワ, サカエ; 矢沢, 篤子; ヤザワ, アツコ; 遠藤, 陽子; エンドウ, ヨウコ; Karasawa, Sakae; Yazawa, Atsuko; Endo, Yoko (国立極地研究所, 1977)
P(論文) 1974年1月7日から2月4日まで,東オングル島で採取した16地点の土壌の理化学性に関する分析を試みた.それによれば東オングル島の土壌は,粒径の大きい粗砂あるいは細砂に属し,土壌が置換できる塩基の最大容量を示す塩基置換容量は,1.15～5.87 me/100 g soil と日本国内の畑地の5分の1程度の値であり,養分保持力が小さく,養分欠乏を起しやすい土質といえた.また全置換性塩基は0.67～12.7 me/100 g soil, 塩基飽和度は43～217%であった.島の東部から西南部にかけては,海塩粒子等の影響と思われる水溶性ナトリウムが高濃度で検出された.東オングル島内で作物生育に適する地点は,島の東中央部のごく狭い地域に限られ,コケ類等の生育地点とはかならずしも一致していなかった. Soil samples were taken at 16 points in East Ongul Island, Antarctica from January 7 to February 4, 1974. The chemical analysis of them obtained the following results: 1) Dissolved cations: 0.10-4.63 me/100 g soil. 2) Cation exchangeable capacity; 1.15-5.87 me/100 g soil. 3) Exchanged cations: Mg 2.81-4.26 me/100 g soil, Ca 0.18-2.16 me/100 g soil, Na 0.01-11.3 me/100 g soil, K 0.01-0.96 me/100 g soil. From the obtained results three areas were distinguished, namely, the area containing much dissolved cations, the area where the degree of base saturation is high, and the area in which the degree of base saturation is adequate for plant growth. departmental bulletin paper